Associations between biased threat interpretations, fear and avoidance of pain and pain‐linked disability in adolescent chronic pain patients. (26th January 2021) - Atkinson‐Jones, K.; Jacobs, K.; Lau, J.Y.F.
Abstract: Background: Biased interpretations of ambiguous bodily threat situations characterize youth with chronic pain, and have been associated with functional disability for this population. Despite predictions by the fear‐avoidance model of chronic pain, that fear and avoidance of pain explain the association between threat perceptions and disability, this has not yet been explored in youth with chronic pain. This study aimed to address this gap by investigating these proposed relationships, in addition to the association between bodily threat interpretations and daily aspects of disability (as well as social, and emotional impairments). Method: Sixty‐eight adolescents aged 11–18 years old with a clinical diagnosis of chronic pain completed an extended version of the Adolescent Interpretations of Bodily Threat task to assess interpretations of bodily and social threat situations, alongside measures of disability and fear and avoidance of pain. Results: Using mediation analysis, fear and avoidance of pain statistically accounted for the relationship between negative bodily threat interpretations and functional disability. Significant associations were also demonstrated between negative bodily threat interpretations and adolescent‐reported impairments in daily, emotional and social impairments. Data revealed a significant relationship between negative social interpretations and daily functional disability. Conclusions: Findings indicate the clinical relevance of bodily and social threat interpretations, and fear and avoidance of pain, for this population and raise further questions regarding the content‐specificity of threat interpretations. Significance: Psychological theories of pain‐associated impact and disability point to fear and avoidance of pain, as well as information‐processing biases. Here, we present novel data showing the clinical relevance of bodily and social threat interpretations in explaining pain‐related disability amongst youth with chronic pain, potentially by shaping fear and avoidance of pain. Longitudinal designs will be required to assess these temporally sensitive mediation pathways.